Effect of supplemental phytase along with various levels of non-phytate phosphorus (NPP) in the diets of broiler chickens - Shalini, Shalini; Chauhan, S S (The Indian Journal of Animal Sciences, 2005)
A 6-week feeding trial was conducted in a factorial design format on 144, day-old broiler chicks to determine the effects of phytase supplementation in the diets containing different Levels of non-phytate phosphorus (NPP). There were 4 dietary NPP levels (0.18, 0.29, 0.40 and 0.52%) and 2 phytase levels (0 and 500 U/kg diet). Observation on growth performance, blood biochemicals and bone mineralization were recorded. Lower dietary NPP levels decreased feed intake and weight gain (135.2 ± 18.8Og) and increased mortality, whereas dietary phytase increased feed intake and weight gain (1477.50 ± 18.80g) significantly (P&lt0.01) and increased the mortality from 28.22 to 13.89%. The serum concentrations of Ca and inorganic P were significantly (P&ltO.O1) increased by phytase supplementation from 6.33 to 7.41 mg/dl respectively. Ash and mineral contents of tibia were linearly decreased as dietary NPP levels reduced but dietary phytase improved the bone mineralization. The improved chick performance was related to an improved utilization of dietrvy P, as confirmed by significantly elevated serum concentration of inorganic P and increased tibia ash cent in birds receiving phytase treated diets. It was concluded that dairy phytase improved the performance, P utilization and bone mineralization of broilers.